DEGREE AND ETIOLOGY OF INTESTINAL PARASITOSIS IN PATIENTS WITH CUTANEOUS LEISHMANIASIS (American Journal of Technology and Applied Sciences, 2024)
In this article, the authors studied the frequency and etiological composition of intestinal parasitosis in 140 patients diagnosed with cutaneous leishmaniasis. According to the results of the study, Giardia lamblia cysts were found in 21.4% of patients with cutaneous leishmaniasis, infection with Enterobius vermicularis in 7.0% of patients, infection with Ascaris lumbricoides in 4.2% of patients, infection with Hymenolepis nana in 5% of patients.